Comprehensive, Evidence-Based, Consensus Guidelines for Prescription of Opioids for Chronic Non-Cancer Pain from the American Society of Interventional Pain Physicians (ASIPP) - Manchikanti, Laxmaiah (Pain physician, 2023)
BACKGROUND: Opioid prescribing in the United States is decreasing, however, the opioid epidemic is continuing at an uncontrollable rate. Available data show a significant number of opioid deaths, primarily associated with illicit fentanyl use. It is interesting to also note that the data show no clear correlation between opioid prescribing (either number of prescriptions or morphine milligram equivalent [MME] per capita), opioid hospitalizations, and deaths. Furthermore, the data suggest that the 2016 guidelines from the Centers for Disease Control and Prevention (CDC) have resulted in notable problems including increased hospitalizations and mental health disorders due to the lack of appropriate opioid prescribing as well as inaptly rapid tapering or weaning processes. Consequently, when examined in light of other policies and complications caused by COVID-19, a fourth wave of the opioid epidemic has been emerging. OBJECTIVES: In light of this, we herein seek to provide guidance for the prescription of opioids for the management of chronic non-cancer pain. These clinical practice guidelines are based upon a systematic review of both clinical and epidemiological evidence and have been developed by a panel of multidisciplinary experts assessing the quality of the evidence and the strength of recommendations and offer a clear explanation of logical relationships between various care options and health outcomes. METHODS: The methods utilized included the development of objectives and key questions for the various facets of opioid prescribing practice. Also utilized were employment of trustworthy standards, and appropriate disclosures of conflicts of interest(s). The literature pertaining to opioid use, abuse, effectiveness, and adverse consequences was reviewed. The recommendations were developed after the appropriate review of text and questions by a panel of multidisciplinary subject matter experts, who tabulated comments, incorporated changes, and developed focal responses to questions posed. The multidisciplinary panel finalized 20 guideline recommendations for prescription of opioids for chronic non-cancer pain. Summary of the results showed over 90% agreement for the final 20 recommendations with strong consensus. The consensus guidelines included 4 sections specific to opioid therapy with 1) ten recommendations particular to initial steps of opioid therapy; 2) five recommendations for assessment of effectiveness of opioid therapy; 3) three recommendations regarding monitoring adherence and side effects; and 4) two general, final phase recommendations. LIMITATIONS: There is a continued paucity of literature of long-term opioid therapy addressing chronic non-cancer pain. Further, significant biases exist in the preparation of guidelines, which has led to highly variable rules and regulations across various states. CONCLUSION: These guidelines were developed based upon a comprehensive review of the literature, consensus among expert panelists, and in alignment with patient preferences, and shared decision-making so as to improve the long-term pain relief and function in patients with chronic non-cancer pain. Consequently, it was concluded – and herein recommended – that chronic opioid therapy should be provided in low doses with appropriate adherence monitoring and understanding of adverse events only to those patients with a proven medical necessity, and who exhibit stable improvement in both pain relief and activities of daily function, either independently or in conjunction with other modalities of treatments. KEY WORDS: Chronic pain, persistent pain, non-cancer pain, controlled substances, substance abuse, prescription drug abuse, dependency, opioids, prescription monitoring, drug testing, adherence monitoring, diversion DISCLAIMER: The guidelines presented are based upon the best available evidence, and do not constitute or represent inflexible treatment recommendations. This document is not intended to be regarded and/or used as a “standard of care.”